2015
DOI: 10.1111/iej.12466
|View full text |Cite
|
Sign up to set email alerts
|

Digital radiographs displayed on different devices: effect on the detection of vertical root fractures

Abstract: The type of display device did not affect the detection of VRFs. Thus, the detection of VRFs can be performed using different screen sizes and resolutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…, Vasconcelos et al . ). In addition, according to the SEDENTEXCT guidelines () and the ESE position statement (European Society of Endodontology ), 3D imaging for root fracture diagnosis should be indicated only if both clinical and conventional radiographic data do not provide adequate information for final diagnosis, which indicates that periapical radiography will remain being important for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…, Vasconcelos et al . ). In addition, according to the SEDENTEXCT guidelines () and the ESE position statement (European Society of Endodontology ), 3D imaging for root fracture diagnosis should be indicated only if both clinical and conventional radiographic data do not provide adequate information for final diagnosis, which indicates that periapical radiography will remain being important for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…A high contrast resolution increases the availability of shades of gray in an image. Theoretically, this could improve diagnosis with more shades of gray in image until a limit considering the ability that the human eye can see and the contemporary computer monitors can support 15 . However, our results showed that spatial resolution seems to be more important than contrast resolution, as SnapShot exhibited better performance but lower contrast resolution when the aluminum wedge was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“… 25 To detect the horizontal root fracture, intraoral radiography is widely used as it is cheap, has high resolution, and is convenient. 26 While interpreting radiographic images, a radiolucent line demonstrating discontinuity of dentine, which is not a shadow of the periodontal ligament, can be diagnostic of root fracture, 27 but subtle fissures in a very early stage without separation of the fragments may not be quantifiable by intraoral radiography. 28 The results of the study suggest that intraoral radiography is not an exact method for detection of horizontal root fracture.…”
Section: Discussionmentioning
confidence: 99%
“… 17 The effect of patient movement on the scans cannot be taken into account, which has a significant effect on the resolution of images 34 and also has the issue of root fillings or various types of post that affect diagnosis. 27 In respect to the selection of an object in the trial, the current study is first research on humans and provides valuable state-of-art research results in the field of Endodontists.…”
Section: Discussionmentioning
confidence: 99%